Enhanced Wound Healing in Diabetic Rat Limbs Using Autologous Mesenchymal Stem Cell Micrografts via the Rigenera® System - Mariza Brandão Palma; Gleydson Breno Alves Cabral Silva; José Sérgio Herculano Gomes da Silva; Livia Maria Marques Pereira; Elton Santos Guedes de Morais; Marcelo Teixeira Westein; Anísio Francisco Soares (Archives of Current Research International, 2024)
Mesenchymal stem cells (MSCs), undifferentiated cells with high proliferative potential, are present in small quantities in bodily secretions and various adult tissues. Their broad distribution and lack of ethical concerns allow for their use in diverse treatments, positioning them as a promising alternative to standard pharmaceutical therapies for wound healing. Although the process of obtaining and culturing MSCs for clinical application remains a challenge, new technologies such as Rigenera® simplify this stage, enabling the direct extraction of MSCs from tissue fragments without extended culturing. This study aimed to evaluate the macroscopic effects of MSCs in wound healing in diabetic rats, considering the pathological characteristics and dysregulation of the inflammatory response that hinder the healing process. Wistar rats were used and divided into four experimental groups: control (CT), control treated with micrografts (CTST), diabetic (DB), and diabetic treated with micrografts (DBST). Lesions of approximately 1 cm² were induced on the hind paws, involving skin, subcutaneous tissue, and muscle. In the treated groups, autologous micrografts obtained with the Rigenera® system were used. Macroscopic parameters such as hyperemia, secretion, granulation tissue formation, and epithelialization were analyzed. The DBST group showed significant advances in tissue reconstruction, with complete tissue restoration observed after 14 days. Thus, the Rigenera® system proved effective in obtaining autologous micrografts to promote tissue regeneration in wounds in diabetic rats